2020
DOI: 10.48550/arxiv.2006.08253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of Spin Relaxation Anisotropy by Spin-Orbit-Coupled Diffusive Spin Motion

Daisuke Iizasa,
Asuka Aoki,
Takahito Saito
et al.

Abstract: Spatiotemporal spin dynamics under spin-orbit interaction is investigated in a (001) GaAs twodimensional electron gas using magneto-optical Kerr rotation microscopy. Spin polarized electrons are diffused away from the excited position, resulting in spin precession because of the diffusioninduced spin-orbit field. Near the cancellation between spin-orbit field and external magnetic field, the induced spin precession frequency depends nonlinearly on the diffusion velocity, which is unexpected from the convention… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Very recently, it was shown that the spin relaxation anisotropy can be controlled by diffusive motion [21], in complement to the extensive literature for stationary spins in GaAs * felixggh@if.usp.br systems [22][23][24][25] including high mobility samples [26,27]. Here, we demonstrate electrical control during drift transport in a 2DEG confined in a wide QW occuping two-subbands.…”
Section: Introductionsupporting
confidence: 55%
“…Very recently, it was shown that the spin relaxation anisotropy can be controlled by diffusive motion [21], in complement to the extensive literature for stationary spins in GaAs * felixggh@if.usp.br systems [22][23][24][25] including high mobility samples [26,27]. Here, we demonstrate electrical control during drift transport in a 2DEG confined in a wide QW occuping two-subbands.…”
Section: Introductionsupporting
confidence: 55%